CHARACTERIZATION OF THE SOL-GEL PROCESS IN THE SYSTEM YxBax+nCu2x+nOδ (x = 1, n=1, x=2, n=3, x=3, n=2): UDC 546.56+54.057 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
With the help of sol-gel technology was obtained superconducting compound number YxBax+nCu2x+nOδ (x=1, n=1; x=2, n=3; x=3, n=2) with sub-micron size particles. As a gel maker in these systems was used citric acid monohydrate. An extensive scheme fusion technology was shown. The process described synthesis using thermal, infrared spectroscopic analysis and scanning electron microscopy. There are some aggregations of microparticles mostly for the phases that are synthesized at higher temperatures. Due to Thermal Analysis of modes were optimized heat treatment samples. According to IR spectroscopy were controlled processes of decomposition of the charge and the formation of the superconducting phase. It was grounded the choice of analysis methods for the starting compounds and the present calculation algorithm for this synthesis. Studies have shown that even at the beginning of the synthesis batch contained no impurity compound allowing argued that the sol-gel synthesis is a promising method that provides high homogeneity of the material the early stages of the synthesis and enables lower temperature and a subsequent heat treatment. The results of electron microscopy showed that due to the relatively low temperature of synthesis occurs the formation of submicron sized particles, while solid-phase techniques facilitate rapid crystal growth due to the formation of liquid phases at high temperature. The principles and ideas described in this paper can be adapted to more complex oxide systems. Thus, in this paper describes how you can achieve chemical homogeneity at the molecular level in multicomponent systems YxBax+nCu2x+nOδ (x=1, n=1; x=2, n=3; x=3, n=2) using sol-gel technology.
Keywords: sol-gel technology; complex oxide compounds; submicron size